Oxidative damage from repeated tissue isolation for subculturing causes degeneration in Volvariella volvacea - Zhao, Fengyun; Wang, Qiaoli; An, XueMing; Tan, Qiangfei; Yun, Jianmin; Zhang, Yubin (Frontiers in Microbiology, 2023)
The fungal fruiting body is the organized mycelium. Tissue isolation and mycelium succession are common methods of fungal species purification and rejuvenation in the production of edible mushrooms. However, repeated succession increases strain degeneration. In this study, we examined the effect of repeated tissue isolation from Volvariella volvacea fruitbodies on the occurrence of degeneration. The results showed that less than four times in succession improved production capacity, however, after 12 successions, the traits indicating strain degeneration were apparent. For instance, the density of aerophytic hyphae, hyphal growth rate and hyphal biomass were gradually reduced, while the hyphae branching was increased. Also, other degenerative traits such as prolonged production cycles and decreased biological efficiency became evident. In particular, after 19 successions, the strain degeneration became so severe no fruiting bodies were produces anymore. Meanwhile, with the increase in successions, the antioxidant enzyme activity decreased, reactive oxygen species (ROS) increased, the number of nuclei decreased, and the mitochondrial membrane potential decreased along with morphological changes in the mitochondria. This study showed that repeated tissue isolation increased oxidative damage in the succession strain due to the accumulation of ROS, causing cellular senescence, in turn, degeneration in V. volvacea strain.